Martes americana Pinel 1792 - Wilson, Don E.; Mittermeier, Russell A. (Zenodo, 2009)
9. American Marten Martes americana French: Martre d’Amérique / German: Fichtenmarder / Spanish: Marta norteamericana Taxonomy. Mustela americanus Turton, 1806, North America. The number of subspecies is debated and here we recognize eight. Subspecies and Distribution. M. a. americana Turton, 1806 — E Canada (Ontario & Quebec) anf NE USA. M. a. abietinoides Gray, 1865 — SW Canada (C British Columbia & SW Alberta) and NW USA (N Montana & Idaho). M. a. actuosa Osgood, 1900 — Alaska and NW Canada (N Alberta, N British Catan, Northwest Territories & Yukon). M. a. atrata Bangs, 1897 — NE Canada (Newfoundland and Labrador). M. a. caurina Merriam, 1890 — W Canada (W British Columbia) and USA (S Alaska & W Washington). M. a. humboldtensis Grinnell & Dixon, 1926 — SW USA (NW California). M. a. kenaiensis Elliot, 1903 — Alaska (Kenai Peninsula). M. a. nesophila Osgood, 1901 — SW Alaska and W Canada (islands off British Columbia, and perhaps along nearby mainland). Descriptive notes. Head-body 36-45 cm (males), 32-40 cm (females), tail 20-23 cm (males), 18-20 cm (females); weight 470-1250 g (males), 280-850 g (females), adult males are about 65% heavier than females. The American Marten has a long, slender body, with short limbs, bushy tail, and large rounded ears. The pelage ranges from light beige to dark brown, and often shows shades of orange. Many individuals have yellow to bright orange throat and upper chest patches. The head is pale gray and the legs and tail are almost black. The feet are fully furred, each digit has a strong claw. There are four pairs of mammae. The skull is long and narrow, with elongated auditory bullae. Dental formula: 13/3,C1/1,P4/4,M 1/2 = 38. Habitat. American Martens are found predominantly in mature conifer or coniferdominated mixed forests. Preferred habitats are mature old-growth spruce-fir communities, with greater than 30% canopy cover, a well-established understory of fallen logs and stumps, and lush shrub and forb vegetation. They avoid large open spaces such as clearcuttings, but may use riparian areas, meadows, forest edges, and rocky alpine areas above the timberline. In the coastal forests of California, American Martens select the largest available patches of old-growth, old-growth and late-mature, or serpentine habitat; dense, spatially extensive shrub cover is a key habitat element. In Alberta, during the winter, American Martens use young forests, and mature/old coniferous and deciduous stands, according to their availability. In the Selkirk and Purcell Mountains of south-west Canada, American Martens were detected in all habitats sampled including recently logged areas, regenerating stands, dry Douglas-fir (Pseudosuga menziesii) forest and subalpine parkland. They selected for greater crown closure and older stands at the finer resolution; no selection for forest structure was detected at the larger resolution except that American Martens selected against increased overstory heterogeneity. They preferred coniferous stands over deciduous-dominated stands and were more abundant in wetter than in dryer areas. In a clearcut boreal landscape in western Quebec, in which black spruce (Picea mariana) is the predominant forest type, American Martens avoid open regenerating stands composed mostly of recent clearcuts with sparse regeneration. They do not select coniferous stands, even those that are mature or overmature, but prefer deciduous and mixed stands, a large proportion of which has a dense coniferous shrub layer. Winter home ranges usually contain less than 30-35% open or closed regenerating stands and more than 40-50% uncut forest. In south-eastern Labrador, American Martens avoid areas with low productivity and low canopy cover (<20%), but show no selection for tree species composition or cover among more productive forests. In eastern Newfoundland, mature coniferous forest is the dominant cover type in most American Marten home ranges and is the only forest type used proportionately more than its availability by resident individuals. Otherforest types used in proportion to their availability include coniferous scrub and insect-defoliated stands; open areas and sites recently disturbed by fire are avoided at this scale. In northern Maine, in an area where trapping and timber harvesting had been excluded for more than 35 years, American Martens were found to use nearly all the available habitat, although during the summer, they preferred stands that had substantial mortality caused by spruce budworm (Choristoneura fumiferana). Mature, well-stocked coniferous forest was the least abundant forest type in the home ranges of both sexes, in both seasons, whereas mature, well-stocked deciduous forest was the most abundant. Food and Feeding. The diet consists mostly of rodents and other small mammals, including voles, mice, chipmunks, squirrels (7amiasciurus and Glaucomys sp.), and lagomorphs, especially the Snowshoe Hare. Other food items include birds, eggs, reptiles, amphibians, invertebrates (insects, earthworms), fruits, and berries. In Newfoundland, Meadow Voles were the most prevalent food item found in scats (80% in summer and 47-5% in winter); Snowshoe Hares occurred in 28% of winter samples, and 16% other food types were found in scats during each season. In the mixed-conifer forests of southern Sierra Nevada, where the American Marten and Fisher are sympatric, the diet of Fishers appeared to include more remains of birds, lizards, hypogeous fungi, and insects than that of American Martens. However, the dietary overlap between these two species was high. The diets of both species were more diverse than previously reported in North America, perhaps due to the absence or rarity of large prey (Snowshoe Hares and North American Porcupines) or to a greater diversity of available prey types in the southern Sierra Nevada. American Martens hunt and find food by constant searching, sometimes in trees, and often tunnel under snow during winter to search for microtines. Activity patterns. Primarily nocturnal and crepuscular, but can be active during the day. Den/rest sites are in hollow logs ortrees, in rock crevices, or in burrows. Large logs, large snags, and large, live spruce and fir trees are important characteristics for den sites in the central Rocky Mountains. Squirrels provide important denning structures as well as prey for American Martens. Movements, Home range and Social organization. American Martens are solitary and partly arboreal, but spend a considerable amount of time on the ground. They can also swim and dive well. The home ranges of males are 2-3 times larger than those of females: up to 45 km ” for males (overall average c. 9 km?) and up to 28 km? for females (overall average c. 3 km?). The degree of overlap of home ranges varies, but generally male home ranges overlap those of several females, and individuals are intolerant of conspecifics of the same sex. In Minnesota, the home ranges of three males were 10-5, 16-6 and 19- 9 km?, and 4- 3 km? for one female; there was considerable overlap between the ranges of two of the males. In Wisconsin, mean winter home range size was 3-29 km?, with the home ranges of males (mean = 4-25 km?) significantly larger than females (mean = 2-32 km?). In Newfoundland, home range estimates were 29-54 km? for males and 15-19 km?* for females. In Labrador, the mean home range for males was 45 km * and 27- 6 km ” for females. In a forest preserve that was closed to trapping, the proportion of males maintaining residency throughout the study period was found to be higher than that of females, indicating that the home ranges of females were more dynamic than the home ranges of males. Neither males nor females adjusted the size of their home ranges among seasons; however, males tended to shift location of their home ranges in response to increases in available space. Females either maintained a high degree of fidelity among seasons or completely abandoned previously established home ranges. Abandonment of existing home ranges by some females may have resulted from stresses associated with a high density in an untrapped population. Population densities vary from 0-5 to 1-7 per km? Breeding. Mating occurs from July to August. Implantation ofthe fertilized eggs into the uterus is delayed for 190-250 days; embryonic development is about 28 days. Total gestation period is thus 220-275 days. The young are born in late March or April, usually in a hollow tree or arboreal cavity; the natal nest is lined with dry vegetation. In the Sierra Madre Range, Wyoming, natal and maternal dens included rock crevices (28%), snags (25%), Red Squirrel (Tamasciurus hudsonicus) middens (19%), and logs (16%). Littersize is one to five, usually two to three. Neonates weigh c. 28 g, open their eyes after 39 days, are weaned after six weeks, and reach adult size after three months. Sexual maturity is attained at 15-24 months. Status and Conservation. Classified as Least Concern in The IUCN Red List. American Martens are considered common in some parts of their range, and are legally harvested for the fur trade. However, by the early 20" century, excessive trapping had severely depleted the American Marten in many areas, particularly in Alaska, Canada, and western United States. Protective regulations subsequently allowed the species to make a comeback in some areas and reintroduction programs have been carried out in Michigan, Wisconsin, and parts of north-eastern USA and south-eastern Canada. Current low numbers or absences in some areas seem attributable to forestry practices; this species is very sensitive to habitat destruction, and clear-cutting can completely eliminate American Martens from an area. The availability of hollow trees for use as resting sites and natal densis especially critical, and logging procedures that eliminate old stumps or older trees may be detrimental to American Marten populations. Bibliography. Buskirk (1984), Buskirk & MacDonald (1984), Clark et al. (1987), Dumyahn & Zollner (2007), Gosse & Hearn (2005), Hagmeier (1961), Mowat (2006), Poole & Graf (1996), Potvin et al. (2000), Powell et al. (2003), Proulx (2006), Raine (1983), Ruggiero et al. (1998), Simon et al. (1999), Slauson et al. (2007), Smith & Schaefer (2002), Soutiere (1979), Wozencraft (2005). : Published as part of Don E. Wilson & Russell A. Mittermeier, 2009, Mustelidae, pp. 564-656 in Handbook of the Mammals of the World – Volume 1 Carnivores, Barcelona :Lynx Edicions on pages 628-629, DOI: 10.5281/zenodo.5714044